Registro da infância à formação acadêmica: reflexão de novas práticas - MARTINS, Maria Madalena Leal (2023)
This memorial corresponds to the work of conclusion of course of the Degree in Pedagogy, where there are reports of my memories, from childhood to academic formation and narrating each moment of the trajectory of my education since childhood, the games, then the school experiences, in the teaching , my teaching work up to university and perspectives. Using the autobiographical method I lead my own story, with truthful accounts of my whole life. The objective of this study was to analyze the contributions of higher education to my training and teaching practice during the course in the university was able to better understand my role as an educator through changes in my personal and professional practice.